2008
DOI: 10.1068/p5585
|View full text |Cite
|
Sign up to set email alerts
|

Speed Constancy and the Perception of Distance

Abstract: The distance-calibration hypothesis states that retinal velocity is scaled by using distance cues, and judged velocity remains unchanged when distance is changed. The relational hypothesis states that judged velocity depends on retinal velocities, and is proportional to judged distance. These hypotheses were compared in three experiments where the movements of the standard stimulus and the comparison stimulus were manipulated by the ratio of the angular velocity of the comparison stimulus to the angular veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…These findings recall an earlier discussion on whether and how our brain estimates object-motion velocity independently of viewing distance; the issue of speed constancy (McKee and Smallman, 1998;Wallach, 1939). Many studies, with some exceptions (Distler et al, 2000;Tozawa, 2008), favored the view that the perception is based on temporal-frequency-based speed coding (Mather et al, 2017;McKee and Smallman, 1998); a useful but suboptimal strategy. Considering also the ubiquitous reliance on retinal velocity rather than the translational velocity in other species (Altshuler and Srinivasan, 2018), it was speculated (McKee and Smallman, 1998) that the human visual system may not have a genuine representation of translational velocity.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…These findings recall an earlier discussion on whether and how our brain estimates object-motion velocity independently of viewing distance; the issue of speed constancy (McKee and Smallman, 1998;Wallach, 1939). Many studies, with some exceptions (Distler et al, 2000;Tozawa, 2008), favored the view that the perception is based on temporal-frequency-based speed coding (Mather et al, 2017;McKee and Smallman, 1998); a useful but suboptimal strategy. Considering also the ubiquitous reliance on retinal velocity rather than the translational velocity in other species (Altshuler and Srinivasan, 2018), it was speculated (McKee and Smallman, 1998) that the human visual system may not have a genuine representation of translational velocity.…”
Section: Introductionsupporting
confidence: 73%
“…Why did these studies fail to find the invariance? One possibility is that the provided visual cues were insufficient to fully compensate for the variation in depth (Distler et al, 2000;Tozawa, 2008). Yet another possibility is that the human visual system essentially lacks the mechanism to fully recover the scale.…”
Section: Introductionmentioning
confidence: 99%
“…These results support the relational hypotheses and clearly advocate against the quantitative hypotheses. However, other studies (Distler et al, 2000;Epstein, 1978;Rock, Hill, & Fineman, 1968;Tozawa, 2008;Zohary & Sittig, 1993) have shown that the perceived distance may play a role in speed constancy. Importantly, in most of these studies, observers had to compare the speed of synthetic stimuli (e.g., bars, dots, gratings, etc.…”
mentioning
confidence: 93%
“…The challenge for these hypotheses is to explain the bias in the perceived speed that appears when an observer compares two different sized stimuli displayed at the same distance (smaller objects are perceived faster), and the almost perfect constancy found when two identical stimuli are displayed at different distances (Brown, 1931; Distler et al, 2000; Epstein, 1978; McKee & Welch, 1989; Tozawa, 2008; Wallach, 1939; Diener et al, 1976; Zohary & Sittig, 1993). Some empirical evidence seems to favor certain interpretations of the relational hypotheses.…”
mentioning
confidence: 99%
“…This cue changes the absolute vertical position of the standard bar relative to the horizon. This type of relative height cue has been shown to be effective for judging relative object distance (Epstein 1966;Wallach and O'Leary 1982;Tozawa 2008). Given the same distance from the observer, a higher object that has smaller angular vertical separation from the horizon should be perceived as farther away than a lower object.…”
mentioning
confidence: 99%